Local knowledge and wisdom in higher education / edited by G.R. (Bob) Teasdale and Zane Ma Rhea - Teasdale, G. R. (G. Robert); Ma Rhea, Zane (Issues in higher education (Oxford, England), 2000)
During the past three decades, there has been a substantial growth in the number of higher education institutions in developing countries. The majority of these institutions have adopted an approach to teaching and research modelled on the universities of the Western world. Consequently, Western processes of knowledge analysis and transmission have largely remained unchallenged as they are implemented in the pursuit of economic modernisation. However, in recent years, there has been a movement to reaffirm the significance of local knowledge and wisdom in education. There is now an urgency to rediscover local knowledge and wisdom as universities and their communities respond to globalisation. "Local Knowledge and Wisdom in Higher Education" presents an insightful account of the role of indigenous knowledge in higher education institutions across a number of societies.